TStudy On Fishing Gears At Pasar Lama Village, Indonesia - Masrur '; Irwandy Syofyan; Isnaniah ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
For purpose to collect information on construction of the fishing gear which was operated by fishermen at Pasar Lama Village, Labuhanhaji district, South Aceh regency, Aceh province. A series survey activity was conducted for observation of fishing gear characteristic data. The data was compared by literature study. The result show that the fishermen was operated four types of fishing gear such as, gillnet, purse seine, hand line and lift net. They have small and large types, according to the main target species. The small type gillnet is called as” salam” and large type is called “tanjap”. The both of gill net have different mesh size and mesh knot, namely single and double English knot. The construction of purse seine consists of webbing, upper line, buoy line, sell ledge, lower line, sinker line, purse line, buoy, sinker, and ring. The construction of lift net consists of fishing, webbing, frame, upper line, towing rope nets and sinker line. The construction of hand line consists of roller, main line, branch line, bait, sinker and hook. Key words : Fishing gear, gillnet, hand line, lift net, purse seine